Ecosystem Approaches in International Business Non-Equity Collaborations and Partnerships in Evolving Global Cities - Permana, Ngadi; Rizal, M. (Studia Ekonomika, 2024)
This qualitative literature review explores ecosystem approaches in international business, focusing on non-equity collaborations and partnerships within evolving global cities. Global cities serve as critical nodes for multinational enterprises (MNEs), facilitating strategic interactions and innovation through diverse collaborations with local firms and stakeholders. The review synthesizes current research to highlight how such collaborations enhance MNEs' competitive advantage by leveraging local knowledge, resources, and market access. Key findings illustrate the role of global city ecosystems in fostering innovation, operational efficiency, and sustainable development for MNEs. However, challenges such as regulatory complexities and institutional misalignments constrain effective collaboration, necessitating adaptive governance and strategic alignment among stakeholders. Future research directions include integrating quantitative analyses to complement qualitative insights, exploring diverse geographic and sectoral contexts, and advancing digital and sustainable strategies within global city ecosystems.